2020
DOI: 10.1093/mnrasl/slaa072
|View full text |Cite
|
Sign up to set email alerts
|

The formation of young massive clusters by colliding flows

Abstract: Young massive clusters (YMCs) are the most intense regions of star formation in galaxies. Formulating a model for YMC formation while at the same time meeting the constraints from observations is, however, highly challenging. We show that forming YMCs requires clouds with densities ≳ 100 cm−3 to collide with high velocities (≳ 20 km s−1). We present the first simulations which, starting from moderate cloud densities of ∼100 cm−3, are able to convert a large amount of mass into stars over a time period of aroun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
4
34
0
Order By: Relevance
“…Furthermore whilst the previous numerical studies do not find large global changes, have found that particularly massive GMCs can form in the presence of stronger, or tidally induced spiral arms (Dobbs et al 2011;Pettitt et al 2018) compared to weaker or flocculent spiral arms. Small scale models of colliding flows also find that strongly converging flows lead to massive clusters (Dobbs et al 2020;. Such conditions would more likely occur in galaxies with stronger spiral arms, or locations in galaxies where localised strongly converging flows occur (Eden et al 2012;Motte et al 2014).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore whilst the previous numerical studies do not find large global changes, have found that particularly massive GMCs can form in the presence of stronger, or tidally induced spiral arms (Dobbs et al 2011;Pettitt et al 2018) compared to weaker or flocculent spiral arms. Small scale models of colliding flows also find that strongly converging flows lead to massive clusters (Dobbs et al 2020;. Such conditions would more likely occur in galaxies with stronger spiral arms, or locations in galaxies where localised strongly converging flows occur (Eden et al 2012;Motte et al 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Since changing galactic dynamics can have a major impact on the formation of stars (e.g. due to colliding flows, Inutsuka et al 2015;Dobbs et al 2020), this is not ideal.…”
Section: Introductionmentioning
confidence: 99%
“…from our previous work (Dobbs et al 2020; hold. Even in the case where the impact of the magnetic field is strongest, whilst we see a delay in star formation, we then see star formation rates which are similar to the other models.…”
Section: Discussionmentioning
confidence: 66%
“…This velocity is chosen so that the collision has a significant effect on star formation, i.e. the collision enhances the star formation rate above that which would occur for isolated clouds (Dobbs et al 2020), but is still consistent with the highest velocities observed for colliding streams in the Milky Way (Motte et al 2014;Fukui et al 2015Fukui et al , 2018. In we show results with different cloud dimensions and collision velocities, but here we focus on varying the magnetic field strength and orientation.…”
Section: Details Of Simulationsmentioning
confidence: 87%
See 1 more Smart Citation